Adaptive Regulation: A Possible Model for Regulation and Innovation in Personal Social Services. Issue 3 (1st December 2020) - Lahat, Lihi; Sabah, Yekoutiel
Abstract: The provision of personal social services in Israel has recently changed, with many services now outsourced to non-governmental organizations. This shift requires the strengthening of regulatory mechanisms, yet the unique characteristics of personal social services make it difficult to create an efficient regulatory framework. By linking insights derived from the literature on regulation to the specific features of these services, this article presents a conceptual model for their regulation. The model incorporates aspects of innovation in the public sector, including a more comprehensive learning and collaborative process and a new rhetorical language. The proposed regulatory approach consists of three stages: mapping, the design of regulatory instruments, and implementation and evaluation. Applied to the Israeli experience here, this approach may also be relevant for other countries.